HIGIENE SANITASI DASAR SERTA PENGETAHUAN, SIKAP DAN TINDAKAN PENJUAL TERHADAP KEPADATAN LALAT PADA KANTIN SEKOLAH DI KECAMATAN SIDAMANIK TAHUN 2015 - julhija -; irnawati marsaulina; nurmaini * (Lingkungan dan Kesehatan Kerja, 2015)
Abstract School hygiene and sanitation is a requisite for healthy school. One of the implementation for healthy school is canteen. Canteen is a comercial place which suplly food and drink for students, teachers and other official. Canteen must accordence requirements of hygiene and sanitation. Basic sanitation of Canteen as a minimum media to supply healthy environment s that can prevented the disease vector such as flies. The purpose of this research is to know the basic of hygiene and sanitation canteen school, knowledge, attitude and action of the seller with the density of housefly population in canteen school. This is a descriptive research, to know the basic of hygiene and sanitation canteen school, knowledge, attitude and action of the seller with the density of housefly population in canteen. This research did on march – juli 2015. The populations of research are 44 owners as subject population and 44 canteens school as object population. The sample are all of population, there are 44 owners of canteen as subject sample and 44 canteens school as object sample. The data is taken by observation sheet of check list, quisioner and fly grill to count density of housefly population. From this research we can see that all of the basic of hygiene and sanitation canteen school is not accordance requeirements. Because many canteen school still don’t have basic sanitation and the criteria of basic sanitation hasn’t been accordance requirement of hygiene and sanitation. The seller knowledge to the density of housefly population is ‘’good’’ (43,2%). The seller attitude to the density of housefly population is ‘’good’’ (70,5%), and action of seller to the density of housefly population is ‘’low’’ (65,9%). The density of housefly population in new water resources of canteen, near etalase and latrine has been requalified. The place of rubish is ‘’low’’ < 2 flies and on the dining tables are ‘’low’’ 29,5% and ‘’medium’’ 2,3%. Hopely the owner of canteen school can increase the basic of hygiene and sanitation and control to the favorite places of flies that create healthy canteen and accordence requirements of canteen school.